Low-speed Impact Ｒesistance Analysis and Numerical Simulation for Glass Fiber Ｒeinforced Aluminum Laminates - LI Xiao-feng; QU Gui-min (Journal of Harbin University of Science and Technology)
Through the drop weight tests on Glass fiber reinforced aluminum laminates being performed with different impact energy at low speed，the curve of impact load，deflection，and energy histories for each tests were obtained. The dynamic response and impact damage evolution of GLAＲE laminates under different impact energy were analyzed. The results show that the damage area of matrix compression under different impact energy increases with the increase of impact energy． At the time of same Impact energy，the tensile damage area of the first and second substrate of the hit plan was far greater than the third and fourth floors，and glass fiber /epoxy resin layer sequence and direction of presoak material were the main factors influencing the laminates low-speed Impact Ｒesistance. The finite element analysis model of low-speed impact of laminates was built based on ABAQUS． The numerical simulation results show that in low energy impact by means of the criterion of ductile damage as a damage criterion of aluminum alloy material is reasonable.